Kajian Arsitektur Kontekstual pada Bangunan Museum Islam Indonesia K.H. Hasyim Asy'ari, Jombang - Danendra Ahmadani Izzur Raihan; Muchlisiniyati Safeyah (Universitas Batanghari Jambi, 2026)
The KH. Hasyim Asy'ari Indonesian Islamic Museum in Jombang is an example of a building that implicitly applies a contextual architectural approach, as seen in its design elements that respond to local culture and the surrounding environment. This study is necessary because the concept is not explained in official documentation, but can be recognized through the form, materials, and architectural style that combine traditional and modern elements. This research refers to Brent C. Brolin's theory of contextual architecture in Architecture in Context as well as related books and journals that cover indicators of a contextual approach and two principles, namely harmony and contrast. The purpose of this study is to identify the principles of contextual architecture at the KH. Hasyim Asy'ari Indonesian Islamic Museum in terms of form, scale, proportion, color, material, and style, as well as to determine whether the approach is harmonious or contrasting with the surrounding context. The method used is deductive qualitative descriptive through data collection and observation with relevant theories to analyze the characteristics and application of contextual architecture in the museum case study. The results show that the museum applies the principle of contrasting contextual architecture according to the indicators formulated from the above theory. These findings contribute to the development of contextual architecture theory in religious culture and can be used as a reference for the design of religious buildings or the layout of other Islamic boarding school areas in Java so that they remain in harmony with local values.